Co-occurrence of OXA-232, RmtF-encoding plasmids, and pLVPK-like virulence plasmid contributed to the generation of ST15-KL112 hypervirulent multidrug-resistant Klebsiella pneumoniae - Wu, Chunyang; Zhou, Ying; Ai, Wenxiu; Guo, Yinjuan; Wu, Xiaocui; Wang, Bingjie; Zhao, Huilin; Rao, Lulin; Wang, Xinyi; Zhang, Jiao; Yu, Fangyou; Wang, Liangxing (Frontiers in Microbiology, 2023)
The emergence of carbapenem-resistant Klebsiella pneumoniae (CRKP) strains and restricted therapeutic options pose a global threat to public health. Aminoglycosides are a wise option choice, which can effectively reduce the mortality rate when combined with β-lactam drugs. However, in this study, we identified a ST15-KL112 CRKP FK3006 which not only exhibited resistance to carbapenems, but also exhibited high level resistance to aminoglycosides. In addition to the multidrug resistant phenotype, FK3006 also owned typical pathogenic characteristic, including hypermucoviscosity and hypervirulence phenotypes. According to the whole-genome sequencing, one pLVPK-like virulence plasmid, and three key resistant plasmids (blaOXA-232, blaCTX-M-15, and rmtF) were observed in FK3006. Compared to other typical ST15 CRKP, the presence of pLVPK-like virulence plasmid (p3006-2) endowed the FK3006 with high virulence features. High siderophore production, more cell invasive and more resistant to serum killing was observed in FK3006. The Galleria mellonella infection model also further confirmed the hypervirulent phenotype of FK3006 in vivo. Moreover, according to the conjugation assay, p3006-2 virulence plasmid also could be induced transfer with the help of conjugative IncFIIK p3006-11 plasmid (blaCTX-M-15). In addition to the transmissible plasmid, several insertion sequences and transposons were found around blaCTX-M-15, and rmtF to generate the mobile antimicrobial resistance island (ARI), which also make a significant contribution to the dissemination of resistant determinants. Overall, we reported the uncommon co-existence of blaOXA-232, rmtF-encoding plasmids, and pLVPK-like virulence plasmid in ST15-KL112 K. pneumoniae. The dissemination threatens of these high-risk elements in K. pneumoniae indicated that future studies are necessary to evaluate the prevalence of such isolates.